Pengaruh Green Marketing, Green Product, Dan Kemajuan Teknologi Terhadap Minat Beli Mahasiswa PTS Di Kota Malang. - Lukman, Moh.; Farida, Eka; Sholehuddin, Sulton (E-JRM : Elektronik Jurnal Riset Manajemen, 2025)
Abstract This study aims to analyze the influence of green marketing, green products, and technological advancements on the purchasing interest of students at Private Universities (PTS) in Malang City. With a student population of approximately 330,000, Malang has significant potential for fostering environmental awareness and social responsibility. The research employs a quantitative method with an explanatory research approach, utilizing questionnaires distributed to PTS students. Multiple linear regression analysis is applied to identify the impact of each independent variable on the dependent variable, which is the students' interest in purchasing eco-friendly products. The results indicate that green marketing, green products, and technological advancements significantly influence students' purchasing interest, both simultaneously and partially. Green marketing is effective in enhancing awareness and purchasing interest, while high-quality green products attract the attention of environmentally conscious students. Additionally, technological advancements, particularly through digital platforms and social media, enable companies to reach their audience more effectively, thus influencing purchasing decisions. These findings provide valuable insights for companies in designing more effective marketing strategies and emphasize the importance of education regarding eco-friendly products to increase awareness among students. This research is expected to contribute to the development of marketing science in the context of sustainability and assist companies in understanding the characteristics of young consumers who are increasingly concerned about environmental issues. Keywords : Green Marketing, Green Product, Dan Kemajuan Teknologi